Обертання тонкої нагрітої пластини за рахунок власного теплового випромінювання - Pipa, V. I.; Liptuga, A. I. (Publishing house "Academperiodika", 2018)
The results of the theoretical investigation of a heated solid plate rotation caused by its own thermal radiation are presented. The rotational moment of the plate with uniform temperature is due to the asymmetry of a recoil of photons of thermal radiation from different areas of its wide faces. The time dependences of the rotation angle of a rectangular plate with stable temperature and at radiative cooling are calculated. The rotation angle dependences on the plate geometric and optical parameters are studied. It is shown that the rotation angle depends nontrivially on the plate thickness because of the thickness-dependent plate emittance. The numerical calculations are performed for a silicon plate. The biggest rotation effect (rotation angle of 118.5∘ for 70 s) is obtained for a mirror black plate 0.1 mm thick at a preset plate temperature of 350 K and a background temperature of 300 K. The considered model can be useful to develop thermal motors, whose rotors consist of a set of heated plates with photon recoil asymmetry.